National Scale-Up of Results-Based Financing in Primary Health Care: The Case of Armenia. Issue 2 (3rd April 2017) - Petrosyan, Varduhi; Melkom Melkomian, Dzovinar; Zoidze, Akaki; Shroff, Zubin Cyrus
Abstract : Abstract —Results-based financing (RBF) has been integrated into the national health care financing system of Armenia covering all primary health care (PHC) facilities in the country. The RBF program contributed to a substantial increase in the utilization of PHC services and improved provider performance. Based on document and literature review and key informant interviews and focus group discussions, this article describes the successful scale-up and integration of RBF into Armenia's primary health care system throughout the period 2000–2015. The article shows how an interaction of contextual factors, actors, and processes contributed to the successful scale-up and integration of RBF into Armenia's primary health care system. Though international agencies, in this case the United States Agency for International Development (USAID), had a significant influence on the introduction and initial design of the RBF scheme, an important enabler was a well-sequenced reform process that included the most politically important stakeholders, including the State Health Agency. Embedding of RBF in national regulatory frameworks and the provision of funds from the national budget were also key contributors to success. Finally, an important enabler to the subsequent scale-up and integration of RBF into the PHC system was its introduction as part of a larger reform of the primary health care system.